Some novel different solutions for Boussinesq-type models including bright, singular, and dark soliton ones - Darvishi, M. T.; Najafi, M.; Rezazadeh, H.; Rezapour, S.; İnç, Mustafa (Soc Mexicana Fisica, 2024)
Some new different kinds of one-soliton solutions for various forms of Boussinesq-type equations are presented in this paper to describe the nonlinear wave phenomena in coastal and ocean areas such as tsunami waves. These one-soliton solutions include bright, dark, and singular ones. The property of each solution in coastal and ocean engineering is explained.
Keywords: Boussinesq-type equation; singular-solution; dark-soliton solution; bright-soliton solution